The Protective Effects of αB-Crystallin on Ischemia-Reperfusion Injury in the Rat Retina - Huan Yan; Yanli Peng; Wei Huang; Liyan Gong; Li Li (Journal of Ophthalmology)
To investigate whether αB-crystallin protects against acute retinal ischemic reperfusion injury (I/R) and elucidate the potential antioxidant mechanisms. Retinal I/R injury was made by elevating the intraocular pressure (IOP) 110 mmHg for 60 min, and αB-crystallin (1 × 10−5 g/L) or vehicle solution was administered intravitreously immediately after I/R injury. The animal was sacrificed 24 h, 1 w, and 1 m after the I/R injury. The retina damage was detected by hematoxylin and eosin (HE) staining and electroretinography (ERG). The level of malondialdehyde (MDA), nitric oxide (NO), and the total superoxide dismutase (T-SOD) was determined. An immunohistochemical study was performed to detect the activation of inducible nitric oxide synthase (iNOS) and NF- (nuclear factor-) kappaB (NF-κB) p65. The decrease of retinal thickness and the number of retinal ganglion cells (RGCs) can be suppressed by αB-crystallin. And the amplitudes of a- and b-wave were remarkably greater without αB-crystallin. Similarly, αB-crystallin also significantly decreased the level of MDA and NO and enhanced the activities of T-SOD. The positive expression of iNOS and NF-kappaB p65 was obviously reduced while treated with αB-crystallin. αB-crystallin can inhibit the expression of NF-κB and its antioxidative effect to protect the retina from I/R injury.